Demographic, Clinical, and Service Utilization Factors Associated with Suicide-Related Visits among Alaska Native and American Indian Adults - Dillard, Denise A. (Suicide Life Threat Behav, 2016)
Alaska Native and American Indian people (AN/AIs) are disproportionately affected by suicide. Within a large AN/AI health service organization, demographic, clinical, and service utilization factors were compared between those with a suicide-related health visit and those without. Cases had higher odds of a behavioral health diagnosis, treatment for an injury, behavioral health specialty care visits, and opioid medication dispensation in the year prior to a suicide-related visit compared to gender, age, and residence (urban versus rural) matched controls. Odds of a suicide-related visit were lower amongst those with private insurance and those with non-primary care ambulatory clinic visits.